The Effect Of Hamzah Fansuri's Mystical Thought To The Muslim Intellectual Tradition In The Archipelago - Fuad Mahbub Siraj (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
This discussion aims to explain further the effect of Hamzah Fansuri's mystical thought to the muslim intellectual tradition in the archipelago. This research is a library research using a historical approach to obtain data and conducting content analysis. This research show that Hamzah Fansuri was the first in the Archipelago who wrote on mystical thoughtin a systematic form that had roots in a strong scientific approach and pure of deviation and perfect in reference to Arabsources. From the works of á¸¤amzah Faná¹£Å«rÄ«, we can see his mystical style of writing which had a distinctive character, in contrast to other Fansuri's who lived in the past. Although the influence of wahdah al-wujud was still strong, Hamzah Fansuri was able to transform the term in Arabic into Malay, so it could be understood by people who were unable to speak Arabic. Hamzah Fansuri provided new technical concepts in Malay; he has made the language fully adequate to discussthe doctrines of philosophical and metaphysical thought formulated by previous Sufis. Hamzah Fansuri is not only as the originator and pioneer of Sufism wujudiyah in the archipelago, but also as laying the foundations of Islamic studies and integration of Islam and culture.